Rescuing companies or their creditors: Understanding the role of the CVA as a rescue procedure in the UK - Morgan, Susan (2022)
This study analyses and discusses the interaction of the key elements contributing to the current use of the Company Voluntary Arrangement (CVA) and the role it plays as part of the rescue culture. The areas discussed include potential issues with the current statutory and regulatory framework; the role of the Insolvency Practitioner; the control exercised by the different classes of creditors; and the impact of company characteristics on the use of the CVA.